Margaretha Stéen; Elaphystrongylosis. A clinical, pathological and taxono-mical study with special emphasis on the infection in moose - Skjenneberg (ed.), Sven (Rangifer, 1992)
Margareta Steen defended her PhD thesis Elaphystrongylosis. A clinical, pathological and taxono-mical study with special emphasis on the infection in moose at the Swedish University of Agriculture, Uppsala, Sweden on December 13, 1991.